The Contribution of Plasma Urea to Total Osmolality During Iatrogenic Fluid Reduction in Critically Ill Patients. Issue 1 (29th October 2021) - Nihlén, Sandra; Frithiof, Robert; Titze, Jens; Kawati, Rafael; Rasmusson, Johan; Rylander, Christian; Pikwer, Andreas; Castegren, Markus; Belin, Anton; Hultström, Michael; Lipcsey, Miklos
Abstract: Hyperosmolality is common in critically ill patients during body fluid volume reduction. It is unknown whether this is only a result of decreased total body water or an active osmole-producing mechanism similar to that found in aestivating animals, where muscle degradation increases urea levels to preserve water. We hypothesized that fluid volume reduction in critically ill patients contributes to a shift from ionic to organic osmolytes similar to mechanisms of aestivation. We performed a post-hoc analysis on data from a multicenter observational study in adult intensive care unit (ICU) patients in the postresuscitative phase. Fluid, electrolyte, energy and nitrogen intake, fluid loss, estimated glomerular filtration rate (eGFR), and estimated plasma osmolality (eOSM) were registered. Contributions of osmolytes Na +, K +, urea, and glucose to eOSM expressed as proportions of eOSM were calculated. A total of 241 patients were included. eOSM increased (median change 7.4 mOsm/kg [IQR−1.9–18]) during the study. Sodium's and potassium's proportions of eOSM decreased ( P < .05 and P < .01, respectively), whereas urea's proportion increased ( P < .001). The urea's proportion of eOSM was higher in patients with negative vs. positive fluid balance. Urea's proportion of eOSM increased with eOSM ( r = 0.63; adjusted for eGFR r = 0.80), but not nitrogen intake. In patients without furosemide and/or renal replacement therapy ( n = 17), urea's proportion of eOSM and eOSM correlated strongly ( r = 0.92). Urea's proportion of eOSM was higher in patients not surviving up to 90 d. In stabilized ICU patients, the contribution of urea to plasma osmolality increased during body water volume reduction, statistically independently of nitrogen administration and eGFR. The shift from ionic osmolytes to urea during body fluid volume reduction is similar to that seen in aestivating animals. ClinicalTrials.org Identifier: NCT03972475. Graphical Abstract: